Disseminating News Releases by Clip Sheets: Sometimes the Old Ways Still Work - Robert E. Thomas (Journal of Applied Communications, 1996)
In an era of electronic information delivery, this article examines the effectiveness of a low cost clip sheet produced since 1920 as a way of providing Missouri-based media news and feature stories about the University of Missouri College of Agriculture, Food and Natural Resources.